Incidencia de tuberculosis, VIH e Índice de Desarrollo Humano en Colombia: un análisis por departamentos 2005-2014 (2023)
Objective: To correlate the incidence of pulmonary tuberculosis, extrapulmonary tuberculosis and HIV with the human development index by departments in Colombia between 2005 and 2014. Methods: Ecological study in 29 departments of Colombia. The incidence data of pulmonary, extrapulmonary and HIV tuberculosis were obtained through the request to departmental health secretaries and data registered in SIVIGILA. The information on the human development index (HDI) was obtained from the United Nations Development Program. The description of the variables was made with measures of central tendency, position, dispersion and 95% confidence intervals. The variation of the disease rates over time was done with the H Kruskal Wallis test. The covariation between the rates of diseases and the HDI was evaluated with scatter plots and Spearman correlation coefficients. In all the analyzes p values lower than 0.05 were considered significant. Results: There is an increase in the incidence of pulmonary tuberculosis and HIV in the period studied. On the other hand, no correlation was found between the HDI with the rate of pulmonary tuberculosis; however, positive and significant correlations with Rho Spearman of 0.320 and 0.324 were found with extrapulmonary tuberculosis and HIV, respectively. Conclusion: this study showed a positive and significant correlation between HIV infection, extrapulmonary tuberculosis and human development index, which indicates that the regions of the country with the highest level of development have the highest infection rates. This information is important for the health authorities to carry out actions that help to understand the causes that explain this phenomenon. © 2019 Asociacion Colombiana de Infectologia. All rights reserved.